Love in the Islamic Religion - Yusuf, Mohammed Remedan (Journal of Islamic Sciences, 2025)
This research explores the subject of love from the perspective of Islamic law, emphasizing the importance of love for living a happy life. The aim of the study is to clarify the Islamic legal ruling on the matter of love, as it is an issue that humans cannot avoid as long as they live a social life. The study employs a descriptive approach to explain the terminology, a deductive approach to infer from texts, and an analytical approach to analyze issues related to love. The research was divided into three sections: the first section explains what falls under praiseworthy love, the second section explains what loving each other for the sake of God entails, and the third section deals with blameworthy love. The research concluded with its most important results, which is that not all love is praiseworthy, and that praiseworthy love is what calls for following the beloved in obedience to God, and that blameworthy love is what leads to the pursuit of desires and the abandoning Islamic values, and that patience in giving up temptations is a virtue for which a person is rewarded.